The history of Isaiah : the formation of the Book and its presentation of the past - Stromberg, Jacob; Hibbard, James Todd (Tübingen : Mohr Siebeck, 2021)
The book of Isaiah is a product of history. The nature of that history and what it means that Isaiah is a product of it are hardly matters of consensus in the field. Nonetheless, Isaianic scholarship has put its collective finger on the crux of the methodological problem. At the heart of an historical understanding of this prophetic book lies a consideration of the word "history" in two distinct but related applications. First, what historical processes led to the book's final form? How did Isaiah become a book? And second, what kind of historical representation does the book offer to the reader? How does Isaiah present the past? For most scholars, answering either question involves asking the other. To understand better the history of Isaiah, this volume of essays devotes itself to these two lines of inquiry and their relationship. The book of Isaiah is a product of history. The nature of that history and what it means that Isaiah is a product of it are hardly matters of consensus in the field. Nonetheless, Isaianic scholarship has put its collective finger on the crux of the methodological problem. At the heart of an historical understanding of this prophetic book lies a consideration of the word "history" in two distinct but related applications. First, what historical processes led to the book's final form? How did Isaiah become a book? And second, what kind of historical representation does the book offer to the reader? How does Isaiah present the past? For most scholars, answering either question involves asking the other. To understand better the history of Isaiah, this volume of essays devotes itself to these two lines of inquiry and their relationship.
PART 3. The Ancient Near East and the History of Isaiah -- Inverting Assyrian propaganda in Isaiah's historiography : writing the Hezekiah-Sennacherib conflict in the light of the Ashurbanipal-Teumman War / Peter Dubovský -- Metamorphoses of a tyrant : Isaiah 14:4b-21 read in its wider context / Joachim Eck -- The Kabod of YHWH : a key Isaianic theme from the Assyrian empire to the eschaton / Judith Gärtner -- A Fortschreibung from the Assyrian crisis of 701 : Isaiah 30:18-26 as an update to Isaiah 30:8-17? / J. Todd Hibbard -- Ashur will be terror stricken : Isaiah 30:27-33 as inverted political prophecy / Reinhard Müller -- Cyrus : a righteousness / Kim Lan Nguyen -- Theological interpretation of Assyrian propaganda in the book of Isaiah / Konrad Schmid -- Go-out from Babylon/there! : a canonical approach to departure in Isaiah 48:20 and 52:11 / Daniel J. D. Stulac -- Reading the final form of Isaiah as a Persian period text / Marvin A. Sweeney -- Decoding Isaiah 13 / H. G. M. Williamson.
Includes bibliographical references and indexes.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Criticism, interpretation, etc